Scripting feminist ethics in teacher education - Forrest, Michelle, 1950-; Wheeldon, Linda, 1947- (Education (University of Ottawa), 2019)
"In an intriguing and original style, these authors offer a rich resource for understanding the history, process, and value of feminist consciousness-raising for teacher-educators and feminist teachers. Critical incidents in today's classrooms involving values relativism, the rush to judgement, witnessing to vulnerability, cyber-bullying, and countering determinism in teacher education and research are analyzed using key concepts from philosophers and feminist theorists. Weaving together personal narrative, dramatization, literary allusion, and philosophical reconstruction, the authors examine and question the place of the personal in the teacher's ethical responsibility for moral deliberation in pluralistic classrooms. This book is of tremendous value for teacher-educators engaged in helping pre-service teachers develop the critical and sensitive capacities needed to be the voice of authority in a classroom. The ethical questions that are raised have repercussions for teaching professional ethics in other caregiving professions. Going to the heart of the teacher's worst fears and assumptions, this unique work offers a new approach to the analysis of case studies in philosophy of education."--